Expecto de gas / Muhammad Fadhil Aiman Abdul Rahman ... [et al.] - Abdul Rahman, Muhammad Fadhil Aiman; Bakeri, Muhamad Hakim; Muhamad Arif, Ain Izzati; Kamaruddin, Nur Khalilah; Samad, Nurfiqah Najihah (2017)
Nowadays, gas is an important thing to have in every household. Expecto de Gas is a project that will reduce a lot of human energy to carry the gas cylinder to somewhere else. Based on the study, most people especially women having a hard time to handle their gas cylinder even though they only change it once or twice a month. The problem is occur when the gas cylinder to be move from one place With kitchen or other places. Someone who is less in power, they just can either push it or roll it to the kitchen. However, this way can cause unwanted incident to happened. So, in order to avoid any unforeseeable incident in the house, the innovated a trolley to carry the gas cylinder more easier, and at the same time act as a small cabinet. Besides, this trolley also can alert the users if there is leakage with their gas. Expecto de Gas is designed in a simple yet sophisticated pattern to suit with the kitchen environment.